The complete mitochondrial genome of the hybrid Cyprinus capio Furong. [Cyprinus carpio L. mirror (♀)×Cyprinus Carpio var. singuonensis (♂)]. Issue 1 (1st January 2016) - Wang, Jinlong; Zou, Li; Jiang, Guomin; Zeng, Ming; Li, Chuanwu; Wu, Yuanan; Wang, Dongwu; Liu, Mingqiu; Liu, Li
Abstract: The complete mitochondrial genome of the hybrid of Cyprinus carpio L. mirror (♀)× Cyprinus Carpio var. singuonensis (♂) was characterized first in this study. The total length of the genome was identical to the female parent as 16, 581 bp, and the overall base composition was 31.80% A, 24.85% T, 27.55% C and 15.80% G, with a slight A + T bias. It contained 13 protein-coding genes (PCGs), 22 transfer RNA genes, 2 ribosomal RNA genes and 2 main non-coding regions (the control region and the origin of the light-strand replication). This study discovered the 99.70% sequence identity between the hybrid and its female parent, which confirmed the maternal inheritance pattern followed by the mitochondrial genome of the hybrid. However, the sequence alignment of mitochondrial genomes between the hybrid and its female parent revealed a total of 47 variable sites in 15 genes or regions, especially 25 sense mutations in 6 PCGs. The complete mitochondrial genome sequence of the hybrid Cyprinus capio Furong may provide an important dataset for further study in mitochondrial inheritance mechanism.